1997
DOI: 10.1007/s000180050053
|View full text |Cite
|
Sign up to set email alerts
|

Increased Na + -H + exchanger activity in the ileal brush-border membrane of spontaneously hypertensive rats

Abstract: In the present study, we have examined the intestinal Na+ transport, through the Na+)-H+ exchanger in ileal brush-border membrane vesicles (BBMV) isolated from spontaneously hypertensive rats (SHR), and normotensive Wistar Kyoto (WKY) rats as a control group. Na+ uptake into ileal BBMV was stimulated the presence of a proton gradient (pH 5.5 inside/pH 7.5 outside) in SHR and WKY rats, resulting in a transient accumulation (overshoot) in both groups of rats. No overshoot was observed in the absence of a pH grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Aberrant NHE3 activity has been implicated as a potential contributing factor in the pathophysiology of other disease states, including hypertension and renal ischemia-reperfusion injuries. Isolated ileum [141] and renal proximal tubules [62] of spontaneously hypertensive rats (SHR) show increased levels of NHE3 activity and protein in brush-border membranes compared with control Wistar-Kyoto (WKY) animals, which may contribute to increased Na + reabsorption and the pathogenesis of hypertension. Similarly, induction of diabetes mellitus in rats-a disease associated with hypertension and renal dysfunction-increases renal brush-border NHE3 activity, which reverses upon insulin treatment [54].…”
Section: Involvement In Pathophysiological Statesmentioning
confidence: 99%
“…Aberrant NHE3 activity has been implicated as a potential contributing factor in the pathophysiology of other disease states, including hypertension and renal ischemia-reperfusion injuries. Isolated ileum [141] and renal proximal tubules [62] of spontaneously hypertensive rats (SHR) show increased levels of NHE3 activity and protein in brush-border membranes compared with control Wistar-Kyoto (WKY) animals, which may contribute to increased Na + reabsorption and the pathogenesis of hypertension. Similarly, induction of diabetes mellitus in rats-a disease associated with hypertension and renal dysfunction-increases renal brush-border NHE3 activity, which reverses upon insulin treatment [54].…”
Section: Involvement In Pathophysiological Statesmentioning
confidence: 99%
“…These reports have described inhibition of active sodium transport (26), and increased passive membrane permeability for sodium in essential hypertension (5). In spontaneously hypertensive rats (SHR), a classical experimental model for the study of hypertension, stimulation of Na ϩ /H ϩ exchanger has been shown compared with their normotensive genetic control, Wistar-Kyoto (WKY) rats (58). Furthermore, similar changes in sodium transport have been found in other hypertensive models, such as Dahl salt-sensitive rats (30,32), Milan hypertensive rats (48), and fructose-fed rats (9).…”
mentioning
confidence: 98%
“…Increased intestinal sodium absorption is associated with increased blood pressure in elderly humans . However, NHE activity is increased in the jejunum and ileum of younger (6–9 weeks) but not older (12 weeks) spontaneously hypertensive rats . NHE2, NHE3, and NHE8 are found at the brush border membrane of the small intestinal epithelium.…”
Section: Gi Tract and Sodium Absorptionmentioning
confidence: 97%
“…64 However, NHE activity is increased in the jejunum and ileum of younger (6-9 weeks) but not older (12 weeks) spontaneously hypertensive rats. 65,66 NHE2, NHE3, and NHE8 are found at the brush border membrane of the small intestinal epithelium. Studies in Nhe2 À/À and Nhe3 À/À mice have demonstrated that NHE3 accounts for most of the neutral NaCl absorption in the small intestine.…”
Section: Gi Tract and Sodium Absorptionmentioning
confidence: 99%